Analysis of spatio‐temporal changes in annual and seasonal precipitation variability in South America‐Chile and related ocean–atmosphere circulation patterns. (22nd December 2015) - Valdés‐Pineda, Rodrigo; Valdés, Juan B.; Diaz, Henry F.; Pizarro‐Tapia, Roberto
ABSTRACT: Establishing relationships between coupled ocean–atmospheric patterns and precipitation accumulation is important to describe and predict spatio‐temporal variability on annual or seasonal scales, and also to evaluate how this variability is influenced by global warming. The objective of this study was to examine the leading modes of interannual and seasonal (summer, autumn, winter, and spring) precipitation variability in South America‐Chile, and their significant relationship to seasonally aggregated gridded data and climatic indices. Applying exhaustive data quality control measures to data from 238 rain gauges with different lengths of records between 1893 and 2013, a new data set was created with the objective of obtaining reliable records for further analysis. A comprehensive analysis through empirical orthogonal functions (EOF) allowed for determination of the leading modes of annual and seasonal precipitation and their main spatial patterns for the whole country. The percentage of explained variance in the relationship between seasonally aggregated indices and the leading modes of precipitation confirmed that most of the interannual and winter precipitation variability in Chile is linked to the seasonal aggregation of El Nino Southern Oscillation (ENSO). The leading modes of summer, autumn, and spring precipitation were mostly linked to seasonal aggregations of the Madden and Julian Oscillation (MJO), and the Antarctic Oscillation (AAO).